Negotiating alternative masculinities in men’s magazines: transitivity in the formation of counter hegemonic identities - Nur Syuhada Mohd Radzi; Kesumawati A. Bakar; Bahiyah Dato’ Hj. Abdul Hamid (Penerbit Universiti Kebangsaan Malaysia, 2021)
With social transformation and male empowerment, the archetypes of traditional masculinity are being deconstructed and rendered obsolete. The changing view of masculinity demands for an exploration of how popular media, particularly men’s magazines rewrite the discourse of masculinity. Attempting to answer the overarching question of ‘what does masculinity mean today?’, this paper explores identity as a linguistic phenomenon. Drawing on both Critical Discourse Analysis (CDA) and Halliday’s Transitivity system of the Systemic Functional Linguistic (SFL) frameworks, we examine ideational meanings realised by lexicogrammatical selections and discourse-semantic-choice involving process types and participants’ role that form counter hegemonic masculinities. This study argues that as men negotiate their identities, magazines play a critical role in challenging patriarchal masculinity and normalising alternative masculine practices via ideologies embedded in a text. The investigation focuses on how transitivity is drawn on to produce counter hegemonic formations and how different enactments of masculinities are articulated in magazine texts to present alternative forms of male identities. Drawing from 584,600-word corpus of selected men’s magazines titles published from 2016 to 2020, findings revealed the use of material, mental, relational and behavioural processes that manifests counter hegemonic identities or non-traditional representation. Evidence from the corpus reflects various projections of men as emotionally vulnerable, aesthetically conscious, domestically competent and antihomophobic. The implication highlights the different ways media language creates and facilitates the changes in masculine practices and how magazine texts infuse or indoctrinate alternative identities as a stable performance of masculinity.